Niemiecki trójgłos w sprawie "Tajemnic Paryża" (Zimmermann, Szeliga, Marks) = German Three -voices on "The Mysteries of Paris" (Zimmermann, Szeliga, Marx) - Libera, Leszek (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
"Mysteries of Paris", like the "Wandering Jew", were widely covered readership in contemporary Germany. Submitted article is a reconstruction of the three most important (and most comprehensive)reviews of "Mysteries of Paris" in the first phase of the reception of this novel in Germany. The authoreschews own assessments, refers only and summarizes the views of the reviewers. The first two arediscussed in the mainstream positive, even enthusiastic reception of "Mysteries of Paris" in Germany.The response was the analytically penetrating and merciless dissection of the views of young KarlMarx.
Keywords: Sue, Eugene (pseud.), Sue, Marie-Joseph (1804-1857); Marks, Karol (Karl Heinrich Marx) (1818-1883); Zimmermann, Wilhelm (1807-1878); Zychlinski, Franz Friedrich Szeliga von (1816-1900); literatura francuska - krytyka